Tunable polaritons of spiral nanowire metamaterials. Issue 1 (2nd January 2022) - Ioannidis, Thanos; Gric, Tatjana; Rafailov, Edik
Abstract : The tunable spiral nanowire metamaterial design at optical frequency is presented, and the surface polaritons are theoretically studied. It was found that the dispersions of the polaritons could be tuned by varying physical dimensions of the spiral nanowire metamaterial. This geometry is unique. Doing so, one may dynamically control the properties of surface polaritons. In addition, the Ferrell–Berreman modes can be excited that is impossible with the regular nanowire metamaterials having the circular cross-section of the nanowires. Herein, the presence of Ferrell–Berreman branches is confirmed by the performed analysis of the metamaterial band structure. It is worthwhile noting, that existence of Ferrell–Berreman modes is possible without epsilon-near-zero (ENZ) regime. The design of devices where Ferrell–Berreman modes can be exploited for practical applications ranging from plasmonic sensing to imaging and absorption enhancement is possible because of the propagation constant revealing subtle microscopic resonances.